2023
DOI: 10.3390/fi15070229
|View full text |Cite
|
Sign up to set email alerts
|

Hybridizing Fuzzy String Matching and Machine Learning for Improved Ontology Alignment

Abstract: Ontology alignment has become an important process for identifying similarities and differences between ontologies, to facilitate their integration and reuse. To this end, fuzzy string-matching algorithms have been developed for strings similarity detection and have been used in ontology alignment. However, a significant limitation of existing fuzzy string-matching algorithms is their reliance on lexical/syntactic contents of ontology only, which do not capture semantic features of ontologies. To address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Neutel and de Boer [151] concluded that BERT performed well for the automatic alignment of two occupational ontologies. Rudwan and Fonou-Dombeu [152] proposed an ontology alignment method that integrates fuzzy string-matching algorithms and the BERT model for conducting an ontology alignment, the BERT model showed promising results.…”
Section: Figure 21 Blstm -Cnn [132] [130]mentioning
confidence: 99%
“…Neutel and de Boer [151] concluded that BERT performed well for the automatic alignment of two occupational ontologies. Rudwan and Fonou-Dombeu [152] proposed an ontology alignment method that integrates fuzzy string-matching algorithms and the BERT model for conducting an ontology alignment, the BERT model showed promising results.…”
Section: Figure 21 Blstm -Cnn [132] [130]mentioning
confidence: 99%
“…There are several fuzzy string-matching algorithms for string similarity detection to explain the degree of similarity between pairs of strings. These include, but are not limited to, Jaro-Winkler, Jaccard, Levenshtein, Longest Common Subsequence (LCS), Term Frequency-Inverse Document Frequency (TF-IDF), N-gram, and many more [26,27]. In our proposed algorithm, we have utilized both Jaccard and Jaro-Winkler in the merging process.…”
Section: Fuzzy String-matching Algorithmsmentioning
confidence: 99%
“…Specifically, the Jaro-Winkler algorithm works well in processing axioms expressions that contain multiple tokens/words [26]. The Jaccard similarity coefficient algorithm was originally designed for set theory applications [27] but has also been adapted to assess the similarity between strings. This algorithm assesses the resemblance of two strings by analyzing their individual characters and identifying shared characters to ascertain their degree of similarity.…”
Section: Fuzzy String-matching Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the fuzzy set is a 'vague boundary set' compared with a crisp set. Fuzzy string/text matching is a method used to find strings that match a pattern approximately (rather than exactly) [49]. In other words, fuzzy string matching is a search that tries to find matches even when users misspell/mispronounce words or enter/pronounce only partial words for the search.…”
Section: Fuzzy Set and Fuzzy String Matching Scorementioning
confidence: 99%